2016
DOI: 10.1108/k-02-2015-0041
|View full text |Cite
|
Sign up to set email alerts
|

The construction of a mobile business application system for ERP

Abstract: Purpose – In today’s complicated and competitive business environment, companies commonly use enterprise resource planning (ERP) systems to integrate management information and enhance efficiency. In recent years, due to the development of cloud computing and portable devices, a new mobility era is starting. The popularity of smartphones and tablet computers has changed the behavior of mobile-phone users and enhanced the rapid development of mobile commerce. ERP companies have discovered this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
1
5
0
1
Order By: Relevance
“…Our study shows that the proposed model explained most of the variance in terms of attitude toward advertisements on sites providing online video services, such as YouTube. The results indicate that the model's appropriateness in the situation of online video advertising is confirmed by the degree to which the findings are in accordance with those of previous investigations in different areas, such as internet advertisements (Brackett and Carr, 2001) and mobile advertisements (Tsang et al , 2004, Tai et al , 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Our study shows that the proposed model explained most of the variance in terms of attitude toward advertisements on sites providing online video services, such as YouTube. The results indicate that the model's appropriateness in the situation of online video advertising is confirmed by the degree to which the findings are in accordance with those of previous investigations in different areas, such as internet advertisements (Brackett and Carr, 2001) and mobile advertisements (Tsang et al , 2004, Tai et al , 2016).…”
Section: Discussionsupporting
confidence: 86%
“…We have several offices and currently we coordinate by physically visiting the offices.In this scenario, one general manager (RMGGM1) suggested how MbUS could assist in improving coordination:
If MbUS is implemented (in my factory), all employees will be connected to the system and I can coordinate jobs without visiting them.
The impact of improved coordination was also reported by Rathore and Ilavarasan (2014) who noted better communication improved coordination in supply chains. A study by Tai et al (2016) also suggested construction of a mobile business application system for ERP improved the selling process in an enterprise. The latest mobile phones are equipped with a myriad of sensors, cameras, and microphones; these features of mobile phones can also assist RMGs offer location‐aware services, improving the supply chain, reducing process loss, and helping with inventory management.…”
Section: Resultsmentioning
confidence: 99%
“…ere are generally two types of data involved in the recommendation system, namely, scoring data and single-type data. e single-type data contains only 0 and 1 data, and the scoring data is distributed in a certain scoring interval, such as the scoring interval of [1,5]. When the recommendation algorithm solves a single-class problem, the following problems need to be considered: first, the problem of sparseness, that is, there is little information related to user selection.…”
Section: Single Recommendation For Artificial Immunitymentioning
confidence: 99%
“…ere are many applications in this area [4]. Companies such as Baidu and Taobao use information such as user search history and cookies generated by visiting websites to calculate the advertisements that each user may be interested in [5]. e video website provides recommendations to users based on the cookie information of the user's browsing.…”
Section: Introductionmentioning
confidence: 99%